Perilaku Ibu Dalam Memilih Dukun Bayi Sebagai Tenaga Penolong Persalinan Di Wilayah Kerja Puskesmas Tembilahan Hulu Tahun 2016: Perilaku Ibu Dalam Memilih Dukun Bayi Sebagai Tenaga Penolong Persalinan Di Wilayah Kerja Puskesmas Tembilahan Hulu Tahun 2016 - alhidayati yati (Jurnal Kesehatan Komunitas, 2017)
Background: Maternal Mortality Rate (MMR) is one indicator of health development in Indonesia. Deliveries by health personnel to be very important in efforts to reduce maternal mortality. Coverage of births attended by skilled health personnel at health centers Tembilahan Hulu has yet to reach the target of 90%. Target Health Center Tembilahan Hulu is 80% but reached only 45%. The number of maternal deaths in health centers Hulu 2016 Tembilahan 1 case and the number of infant mortality as much as 5 case, one cause of death is handled by TBAs. Objective: to know the mother's behavior in selecting birth attendants in health centers working area Tembilahan Hulu. Design: Qualitative research, to obtain in-depth information about how the Mother Behavior in Choosing Auxiliary Power Delivery at Puskesmas Tembilahan Hulu 2016. Methods: This study used a qualitative descriptive method, which is an approach to research that revealed certain social situations to describe reality correctly, formed by words based on the techniques of collecting and analyzing relevant data obtained from the natural situation. Results and Discussion: Research shows that mothers choose birth attendants decision is closely linked to the knowledge, attitudes, social culture, access to health services, family support. Conclusions: The behavior of mothers in selecting birth attendant is still a lot to TBAs compared to the health worker / midwife.